FANCD2-dependent mitotic DNA synthesis relies on PCNA K164 ubiquitination - Wendy Leung; Ryan M. Baxley; Emma Traband; Ya-Chu Chang; Colette B. Rogers; Liangjun Wang; Wesley Durrett; Kendall S. Bromley; Lidia Fiedorowicz; Tanay Thakar; Anika Tella; Alexandra Sobeck; et al. (Cell Reports, 2023)
Summary: Ubiquitination of proliferating cell nuclear antigen (PCNA) at lysine 164 (K164) activates DNA damage tolerance pathways. Currently, we lack a comprehensive understanding of how PCNA K164 ubiquitination promotes genome stability. To evaluate this, we generated stable cell lines expressing PCNAK164R from the endogenous PCNA locus. Our data reveal that the inability to ubiquitinate K164 causes perturbations in global DNA replication. Persistent replication stress generates under-replicated regions and is exacerbated by the DNA polymerase inhibitor aphidicolin. We show that these phenotypes are due, in part, to impaired Fanconi anemia group D2 protein (FANCD2)-dependent mitotic DNA synthesis (MiDAS) in PCNAK164R cells. FANCD2 mono-ubiquitination is significantly reduced in PCNAK164R mutants, leading to reduced chromatin association and foci formation, both prerequisites for FANCD2-dependent MiDAS. Furthermore, K164 ubiquitination coordinates direct PCNA/FANCD2 colocalization in mitotic nuclei. Here, we show that PCNA K164 ubiquitination maintains human genome stability by promoting FANCD2-dependent MiDAS to prevent the accumulation of under-replicated DNA.